The Validation of the Free Fantasy Questionnaire for Children and Adolescents: From Imaginary Playmate to “Dreamtime” - Donfrancesco, Renato; Vezzani, Claudio; Pinto, Giuliana; Bigozzi, Lucia; Dibenedetto, Angela; Melegari, Maria Grazia; Gregori, Paola; Andriola, Elda; Di Roma, Francesca; Renzi, Alessia; Tambelli, Renata; Di Trani, Michela (Frontiers in Psychology, 2019)
Fantasy in children is a precocious and important skill. In normal subjects some imaginative events, very close to hallucinations (perception-like experiences), have been found. Therefore, a better knowledge on both fantasy and the difference between imagination and the external world is needed. The aims of this study are: a) to validate a new questionnaire for fantasy in children and adolescents; b) to test its clinical application in ADHD children. 1.707 subjects aged 8-18 years were enrolled: 1557 were recruited from a survey in six schools, whereas 150 subjects were recruited in an ADHD Centre. They filled out a new questionnaire, the Free Fantasy Questionnaire for Children and Adolescents, FFQ. Statistical analyses were performed to validate the FFQ and to study five parameters of fantasy. Analyses showed good properties of the FFQ as regards factor structure and reliability. Descriptive analysis showed that: 10% of the adolescents frequently have fantasy with paracosmos and 9.5% sometimes have a fantasy with an imaginary relatives. Moreover, in the 64.3% of subjects of primary school, in the 34.5% of lower-secondary, and in the 27.4% of upper-secondary school Perception-like experiences, involving invisible but real personages, were found. Quality of fantasy and Lack of control on imagination are correlated with a high score in the Reality/Unreality Dimension and Perception-like experiences. As regards ADHD subjects, the 40% of the group showed Perception-like experiences: the 21.66% of them reported a very high score in the dimension Reality/Unreality, have some dissociative symptoms, and the 3.33% presented a clear dissociative identity disorder. All were free from psychosis or neurologic disorders. A new questionnaire to study fantasy in children and adolescents was validated. Many children and adolescents of the general population declared Perception-like experiences. These events seem to be specific, and probably normal, features of the mind; they could be better named as “Dreamtime”, whereas only in extreme conditions they could represent a risk for dissociation.